2018
DOI: 10.1111/tid.12875
|View full text |Cite
|
Sign up to set email alerts
|

Dengue fever in renal allograft recipients: Clinical course and outcome

Abstract: Clinical manifestations of dengue infection in renal transplant recipients were similar to that in general population. However, leucopenia necessitating temporary withdrawal of immunosuppression was common. Renal dysfunction was frequent but completely reversible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 11 publications
3
12
1
Order By: Relevance
“…According to published data, CHIKV in solid organ transplant recipients seems to have a benign course and favorable outcome (19,20), whereas data for DENV in these patients are less clear. Case descriptions report uncomplicated outcomes, whereas a recent literature review reported a significantly higher incidence of severe dengue and a higher mortality rate among transplant patients with dengue (21)(22)(23). A recent report of DENV, ZIKV, and CHIKV infections diagnosed in hematopoietic stem cell transplant recipients and oncohematologic patients found prolonged viremia in those with DENV and viruria in those with ZIKV; the most common complication was thrombocytopenia, but all patients survived without sequelae (24).…”
Section: Discussionmentioning
confidence: 99%
“…According to published data, CHIKV in solid organ transplant recipients seems to have a benign course and favorable outcome (19,20), whereas data for DENV in these patients are less clear. Case descriptions report uncomplicated outcomes, whereas a recent literature review reported a significantly higher incidence of severe dengue and a higher mortality rate among transplant patients with dengue (21)(22)(23). A recent report of DENV, ZIKV, and CHIKV infections diagnosed in hematopoietic stem cell transplant recipients and oncohematologic patients found prolonged viremia in those with DENV and viruria in those with ZIKV; the most common complication was thrombocytopenia, but all patients survived without sequelae (24).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there have been two new publications. In one, there were 11 cases in Brazil with no long-term damage to the patients or to the grafts [37] and, in the second, there were 20 cases in India with 40% of transient renal dysfunction, and 5% of death attributed to the DI [38].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, because the intensity of immunosuppression does not determine the outcome of most patients, and because there is no specific therapy for dengue infection in transplant recipients, early diagnosis and supportive treatment are currently available tools for better clinical management 36, 41…”
Section: Denguementioning
confidence: 99%